2016
DOI: 10.1038/srep23525
|View full text |Cite
|
Sign up to set email alerts
|

Effect of GLP-1 Receptor Activation on Offspring Kidney Health in a Rat Model of Maternal Obesity

Abstract: Maternal obesity is associated with an increased risk of chronic disease in offspring, including type 2 diabetes (T2D). Exendin-4 (Exd-4) activates the glucagon like peptide-1 (GLP-1) receptor thereby decreasing serum glucose levels and body weight. In addition, Exd-4 has been shown to reduce renal and cardiac complications in experimental models of T2D. We hypothesized that treatment with Exd-4 would ameliorate the detrimental effects of maternal and diet-induced obesity on renal characteristics in offspring.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
53
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 34 publications
(39 reference statements)
7
53
0
1
Order By: Relevance
“…Studies, including our own, have shown that the offspring of obese mothers are significantly predisposed to obesity (20,(25)(26)(27)(28). In our previous studies in rodents, maternal obesity increased fat mass in the offspring, and this effect was further amplified when the offspring consumed a high-fat diet after weaning (20,28). Additionally, maternal obesity increases the offspring's risk of dysglycemia, diabetes, and hypertension, which may propagate renal dysfunction in later life (4).…”
Section: Fetal Programming Maternal Transmission Of Disease and Epimentioning
confidence: 80%
See 2 more Smart Citations
“…Studies, including our own, have shown that the offspring of obese mothers are significantly predisposed to obesity (20,(25)(26)(27)(28). In our previous studies in rodents, maternal obesity increased fat mass in the offspring, and this effect was further amplified when the offspring consumed a high-fat diet after weaning (20,28). Additionally, maternal obesity increases the offspring's risk of dysglycemia, diabetes, and hypertension, which may propagate renal dysfunction in later life (4).…”
Section: Fetal Programming Maternal Transmission Of Disease and Epimentioning
confidence: 80%
“…Maternal obesity also plays a significant role in the fetal programming of several adult chronic diseases. Studies, including our own, have shown that the offspring of obese mothers are significantly predisposed to obesity (20,(25)(26)(27)(28). In our previous studies in rodents, maternal obesity increased fat mass in the offspring, and this effect was further amplified when the offspring consumed a high-fat diet after weaning (20,28).…”
Section: Fetal Programming Maternal Transmission Of Disease and Epimentioning
confidence: 81%
See 1 more Smart Citation
“…Indeed, we have previously shown that inflammatory cytokines including IL-6, MCP-1 and TGFβ are increased in the serum of rat offspring of obese mothers, as well as in their kidneys1433. Thus, exposure to maternal obesity may prime offspring towards a pro-inflammatory state, thereby increasing their susceptibility to complications of obesity and kidney disease at a later stage.…”
Section: Discussionmentioning
confidence: 98%
“…The intake of abundant saturated fatty acids resulted in ERS in the intestines and decreased GLP-1 production [25], suggesting that exogenous GLP-1 may reduce the injury. GLP-1 receptor analog remarkably decreased markers of inflammation, oxidative stress, and fibrosis in the kidneys of maternal obesity mice [26]. GLP-1 decreased BIP and p-eIF2α protection against ER stress-induced cell apoptosis-associated transcription factor CHOP in pancreatic INS-1 cells in Akita mice [23], while Cunha et al [27] reported that GLP-1R treatment increased ATF4-CHOP expression in vitro .…”
Section: Discussionmentioning
confidence: 99%